Effect of adjuvants on the antibody response of mice to Bothrops asper (Terciopelo) snake venom - Rucavado, Alexandra (1996)
The adjuvant properties of several immunostimulant molecules on the murine antibody response to Bothrops asper snake venom were evaluated. Mice receiving venom together with either sodium alginate, calcium alginate, aluminum hydroxide, muramyl dipeptide, killed Brucella abortus or B. abortus smooth lipopolysaccharide developed a similar antibody response. Despite the fact that in some cases animals injected with venom and Salmonella montevideo lipopolysaccharide developed a significantly higher antibody titer when compared to other experimental groups, no statistically significant differences were observed in most of the comparisons.